Surface hyperbranched modified fiber, preparation method of surface hyperbranched modified fiber, modified polyacrylate adhesive and application of modified polyacrylate adhesive
By hyperbranching modification on the surface of aramid fibers, nanometal oxide particles are coated to form an organic-inorganic hybrid system, the problem of poor flame retardant performance of existing aerogel packaging composites is solved, and the efficient flame retardant and heat resistance improvement of polyacrylate adhesives is achieved.
Patent Information
- Application Number
- CN202411864261.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-17
- Publication Date
- 2025-03-07
AI Technical Summary
The flame retardant performance of existing aerogel packaging composite materials is poor, making it difficult to effectively prevent thermal runaway and combustion of new energy vehicle batteries.
The surface hyperbranched modified fibers are used, including aramid fibers coated with nanometal oxide particles, and the nanometal oxide particles are grafted through hyperbranched polysiloxane to form an organic-inorganic hybrid system to improve the flame retardant performance of the fibers.
It significantly improves the flame retardant performance of polyacrylate adhesives to reach V0 level, enhances its heat resistance and mechanical properties, and effectively prevents thermal runaway and combustion of the battery.
Smart Images

Figure BDA0005196495580000021 
Figure BDA0005196495580000041 
Figure BDA0005196495580000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of adhesives, and in particular relates to a surface hyperbranched modified fiber and a preparation method thereof, a polyacrylate adhesive and an application thereof. Background Art
[0002] With the continuous upgrading of global energy conservation and emission reduction requirements, the market share of new energy vehicles has gradually increased. At present, the main source of new energy vehicle power systems is lithium-ion batteries. After years of development, they have been significantly improved, but under the current conditions, there is still a risk of explosion and combustion. Accidents of electric vehicles catching fire and exploding due to battery "thermal runaway" are common. Aerogel encapsulation glue, as a power battery insulation material between battery cells, can reduce the risk of combustion of new energy vehicles and improve driving safety.
[0003] Aerogel encapsulation glue is a packaging material for aerogels. It is a special packaging material that has the functions of heat insulation, flame retardancy, buffering and thermal runaway protection between new energy passenger car battery cells and modules. It has the characteristics of good stability and high durability. This encapsulation glue is usually used for packaging in high temperature and high humidity environments. It has a low expansion coefficient, excellent fire resistance, high temperature resistance and good thermal shock resistance; it can also be used in chip packaging to prevent the chip from moisture and contamination while maintaining the good performance of the chip. It can also be used in aerogel composites of ceramic fiber substrates and pre-oxidized silk substrates. These materials are made by embedding silicone frame lamination processing technology, and are used for heat insulation, flame retardancy, buffering, thermal runaway protection, etc. between high-end new energy passenger car battery cells and modules. However, the above-mentioned aerogel composite materials still have the defect of poor flame retardancy. Summary of the invention
[0004] The purpose of the present invention is to provide a surface hyperbranched modified fiber and a preparation method thereof, a polyacrylate adhesive and an application thereof. The polyacrylate adhesive prepared using the surface hyperbranched modified fiber of the present invention has excellent flame retardant properties and can be applied to gas condensation packaging materials.
[0005] In order to achieve the purpose of the present invention, the present invention provides the following technical solutions:
[0006] A surface hyperbranched modified fiber comprises aramid fiber and hyperbranched polysiloxane grafted with nano metal oxide particles and coated on the aramid fiber.
[0007] Preferably, the structure of the hyperbranched polysiloxane is as shown in Formula I:
[0008]
[0009] Preferably, the nano metal oxide particles are calcium oxide-doped cerium oxide particles;
[0010] The mass ratio of calcium oxide to cerium oxide is 2-15:1-2;
[0011] The particle size of the nano metal oxide particles is 100-300 nm.
[0012] Preferably, the mass ratio of the hyperbranched polysiloxane to the aramid fiber is 200-400:1-2; the mass ratio of the nano metal oxide particles to the hyperbranched polysiloxane is 5-15:1-3.
[0013] The present invention also provides a method for preparing the surface hyperbranched modified fiber described in the above technical solution, comprising the following steps:
[0014] Aramid fibers are subjected to amino modification to obtain amino fibers;
[0015] The amino fiber is subjected to methoxylation modification to obtain methoxylated fiber;
[0016] The methoxylated fiber, the hydroxylated metal oxide and the first acid reagent are mixed to perform metal oxide modification to obtain metal oxide coated fibers;
[0017] The metal oxide coated fiber, γ-glycidyloxypropyltrimethylsilane and a second acid reagent are mixed and subjected to polycondensation reaction to obtain the surface hyperbranched modified fiber.
[0018] Preferably, the temperature of the amination modification is 40-80°C and the time is 3-8h;
[0019] The temperature of the methoxylation modification is 60 to 110° C. and the time is 12 to 18 hours;
[0020] The metal oxide modification temperature is 60-100°C and the time is 6-12h;
[0021] The temperature of the polycondensation reaction is 60-90° C. and the time is 5-12 hours.
[0022] The present invention provides a polyacrylate adhesive, which comprises, by weight, 10 to 40 parts of the surface hyperbranched modified fiber described in the above technical solution or the surface hyperbranched modified fiber prepared by the preparation method described in the above technical solution, 2 to 5 parts of a flame retardant and 100 parts of polyacrylate.
[0023] Preferably, the polyacrylate comprises the following preparation raw materials by weight:
[0024] 50-70 parts of soft monomer, 10-25 parts of hard monomer, 1-5 parts of functional monomer, 0.5-1 parts of initiator, 0.5-3 parts of crosslinking agent and 50-70 parts of organic solvent.
[0025] Preferably, the soft monomer includes one or more of butyl acrylate, isooctyl acrylate, ethyl acrylate and lauryl acrylate;
[0026] The hard monomer includes one or more of vinyl acetate, acrylic acid, acrylamide, methyl acrylate and methyl methacrylate;
[0027] The functional monomers include one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl methacrylate and N-hydroxyacrylamide.
[0028] The present invention also provides the use of the polyacrylate adhesive described in the above technical solution in packaging materials.
[0029] The present invention provides a surface hyperbranched modified fiber, comprising aramid fiber and hyperbranched polysiloxane grafted with nano metal oxide particles coated on the aramid fiber. The aramid fiber itself is resistant to high temperatures, has high strength, and has excellent electrical insulation properties. It has a good dispersion effect in polyacrylate, and constructs a barrier to enhance the heat resistance of polyacrylate. At the same time, the aramid fiber itself has good stability and can still maintain structural stability in high temperature environments, thereby ensuring the stable performance of the polyacrylate adhesive. The invention modifies the surface of aramid fiber, forms an organic-inorganic hybrid system by grafting nano metal oxide particles with hyperbranched polysiloxane generated in situ, forms a dense coating layer on the fiber surface in the form of chemical bonds of hyperbranched polysiloxane grafting and nano metal oxide particles, thereby improving the flame retardant performance of the aramid fiber, and there is a chemical force between the Si-O bond of the hyperbranched polysiloxane and the metal atoms in the nano metal oxide particles. The hyperbranched polysiloxane in the outer layer of the nano metal oxide particles helps to break the Si-O bond and the chemical bond between Si-O and the metal atom during the combustion process, not only absorbs heat energy, but also provides more protection on the basis of the dual protection of the organic layer and the inorganic layer, and shows an effective synergistic effect in improving the flame retardant performance of the aramid fiber. The adhesive prepared by using the surface hyperbranched modified fiber of the invention has a flame retardant performance reaching V0 level.
[0030] In addition, hyperbranched polysiloxane grafted with nano-metal oxide particles can improve the bonding properties of the aramid fiber surface, enabling it to be better mixed with polyacrylate, thereby improving the mechanical properties of the adhesive. DETAILED DESCRIPTION
[0031] The invention provides a surface hyperbranched modified fiber, comprising aramid fiber and hyperbranched polysiloxane grafted with nano metal oxide particles and coated on the aramid fiber.
[0032] In the present invention, the aramid fiber is para-aramid fiber; the aramid fiber may be aramid fiber paper.
[0033] In the present invention, the structure of the hyperbranched polysiloxane is shown in Formula I:.
[0034]
[0035] In the present invention, the hyperbranched polysiloxane is a macromolecular structure, which makes the movement between molecular chains relatively difficult, so that the molecular chain movement is relatively slow compared to small molecules when heated, and the molecular chain breakage can also absorb more energy, thereby improving various performances of the product.
[0036] In the present invention, the nano metal oxide particles are calcium oxide-doped cerium oxide particles; the mass ratio of calcium oxide to cerium oxide is 2-15:1-2, and in a specific embodiment, it can be 10:1.5 or 14.9:1.11; the particle size of the inorganic metal particles is 100-300nm, and in a specific embodiment, it can be 150nm or 200nm.
[0037] In the present invention, the mass ratio of the hyperbranched polysiloxane to the aramid fiber is 200-400:1-2, and in a specific embodiment, it can be 250:1 or 200:1.5; the mass ratio of the nano metal oxide particles to the hyperbranched polysiloxane is 5-15:1-3, and in a specific embodiment, it can be 10:1, 15:2 or 10:3. The particle size of the nano metal oxide particles in the present invention is nanometer-scale, which can make the nano metal oxide particles disperse more evenly.
[0038] The present invention also provides a method for preparing the surface hyperbranched modified fiber described in the above technical solution, comprising the following steps:
[0039] Aramid fibers are subjected to amino modification to obtain amino fibers;
[0040] The amino fiber is subjected to methoxylation modification to obtain methoxylated fiber;
[0041] The methoxylated fiber, the hydroxylated metal oxide and the first acid reagent are mixed to perform metal oxide modification to obtain metal oxide coated fibers;
[0042] The metal oxide coated fiber, γ-glycidyloxypropyltrimethylsilane and a second acid reagent are mixed and polycondensed to obtain the surface hyperbranched modified fiber.
[0043] The present invention performs amino modification on aramid fiber to obtain amino fiber. In the present invention, the reagent used for the amino modification is sodium hydroxide-ethanol solution; the solid-liquid ratio of sodium hydroxide and ethanol in the sodium hydroxide-ethanol solution is 5-15g:80-120mL, and in a specific embodiment, it can be 10.5g:120mL; the mass ratio of the aramid fiber and sodium hydroxide is 0.1-0.3:8-12, and in a specific embodiment, it can be 0.1:10.5; the temperature of the amino modification is 40-80°C, and in a specific embodiment, it can be 60°C or 70°C; the time is 3-8h, and in a specific embodiment, it can be 5h or 6h; the amino modification also includes washing and drying in sequence; the washing is water washing, and the present invention has no special restrictions on the drying conditions.
[0044] In the present invention, the aramid fiber is washed and dried in sequence before amino modification; the reagents used for washing are acetone, petroleum ether and deionized water in sequence; the washing method is reflux washing for 3 to 5 hours; the drying temperature is 80 to 100°C and the drying time is 8 to 12 hours.
[0045] After obtaining the amino fiber, the present invention performs methoxylation modification on the amino fiber to obtain methoxylated fiber. In the present invention, the reagent used for the methoxylation modification is a mixed solution of γ-glycidyloxypropyltrimethoxysilane and an organic solvent; the organic solvent is ethanol, and in a specific embodiment, it can be anhydrous ethanol; the solid-liquid ratio of the amino fiber and γ-glycidyloxypropyltrimethoxysilane is 0.1-0.3g:10-30mL, and in a specific embodiment, it can be 0.1g:30mL; the temperature of the methoxylation modification is 60-110°C, and in a specific embodiment, it can be 70°C or 100°C; the time is 12-18h, and in a specific embodiment, it can be 12h; the methoxylation modification is carried out under a protective gas atmosphere; the protective gas is nitrogen.
[0046] After obtaining the methoxylated fiber, the present invention mixes the methoxylated fiber, the hydroxylated metal oxide and the first acid reagent to perform metal oxide modification to obtain the metal oxide coated fiber. In the present invention, the first acid reagent is hydrochloric acid; the mass concentration of the hydrochloric acid is 30-45%, and in a specific embodiment, it can be 38%. In the metal oxide modification process of the present invention, the methoxyl group on the methoxylated fiber is combined with the hydroxyl group of the hydroxylated metal oxide.
[0047] In the present invention, the preparation method of the hydroxylated metal oxide comprises the following steps:
[0048] Dissolving a water-soluble cerium salt and a water-soluble calcium salt in water respectively to obtain a mixed solution;
[0049] The mixed solution is adjusted to be alkaline, and then the first hydrogen peroxide is added to precipitate, and the obtained solid product is calcined after solid-liquid separation to obtain a bimetallic oxide;
[0050] The bimetallic oxide and the second hydrogen peroxide are mixed and subjected to hydroxylation modification to obtain the hydroxylated metal oxide.
[0051] In the present invention, the water-soluble cerium salt is cerium chloride; the water-soluble calcium salt is calcium chloride; the mass ratio of the water-soluble cerium salt to the water-soluble calcium salt is 2-15:1-2; the mass ratio of the water-soluble cerium salt to sodium hydroxide is 14.9-16:6-8; the present invention has no special limitation on the concentrations of the first hydrogen peroxide and the second hydrogen peroxide, and the solid-liquid ratio of the water-soluble cerium salt to the first hydrogen peroxide is 14.9-16g:3-5mL; the reagent for adjusting the alkalinity of the mixed solution is sodium hydroxide; the temperature of the precipitation is 40-60°C and the time is 20-24h; the solid-liquid separation method is suction filtration; after the solid-liquid separation, the obtained solid product is washed and dried in sequence; the temperature of the calcination is 700-850°C and the time is 1-3h; the temperature of the hydroxylation modification is 60-80°C and the time is 6-12h.
[0052] In the present invention, the mass ratio of the methoxylated fiber, the hydroxylated metal oxide and the first acid reagent is 0.1-0.3:0.5-1:1-3, and in a specific embodiment, it can be 0.1:0.595:1; the temperature of the metal oxide modification is 60-100°C, and in a specific embodiment, it can be 80°C; and the time is 6-12h.
[0053] After obtaining the metal oxide coated fiber, the present invention mixes the metal oxide coated fiber, γ-glycidyloxypropyltrimethylsilane and a second acid reagent, and performs a polycondensation reaction to obtain the surface hyperbranched modified fiber. In the present invention, the second acid reagent is consistent with the first acid reagent; the mass ratio of the metal oxide coated fiber, γ-glycidyloxypropyltrimethylsilane and the second acid reagent is 0.1-0.3:10-50:5-10, and in a specific embodiment, it can be 0.1:47.2:5.4; the temperature of the polycondensation reaction is 60-90°C, and in a specific embodiment, it can be 70 or 80°C; the time is 5-12h; the polycondensation reaction also includes washing and drying in sequence; the washing is water washing, and the present invention has no special restrictions on the conditions of the drying.
[0054] The present invention also provides a polyacrylate adhesive, which comprises, by weight, 10 to 40 parts of the surface hyperbranched modified fiber described in the above technical solution, 2 to 5 parts of a flame retardant and 100 parts of polyacrylate.
[0055] In the present invention, the polyacrylate adhesive includes 10 to 40 parts of surface hyperbranched modified fibers by weight. In a specific embodiment, the amount may be 15 parts, 20 parts, 25 parts, 30 parts or 35 parts.
[0056] In the present invention, the polyacrylate adhesive includes 2 to 5 parts of a flame retardant by weight, and in a specific embodiment, it can be 3 parts, 3.5 parts or 4 parts; the flame retardant is aluminum hydroxide.
[0057] In the present invention, the polyacrylate adhesive comprises 100 parts of polyacrylate by weight; the raw materials for preparing the polyacrylate comprise: 50 to 70 parts of soft monomer, 10 to 25 parts of hard monomer, 1 to 5 parts of functional monomer, 0.5 to 1 part of initiator, 0.5 to 3 parts of crosslinking agent and 50 to 70 parts of organic solvent;
[0058] The soft monomer includes one or more of butyl acrylate, isooctyl acrylate, ethyl acrylate and lauryl acrylate;
[0059] The hard monomer includes one or more of vinyl acetate, acrylic acid, acrylamide, methyl acrylate and methyl methacrylate;
[0060] The functional monomers include one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl methacrylate and N-hydroxyacrylamide.
[0061] In the present invention, the raw materials for preparing the polyacrylate include 50 to 70 parts of soft monomers by mass, and in specific embodiments, may be 55 parts, 60 parts or 65 parts; the soft monomers include one or more of butyl acrylate, isooctyl acrylate, ethyl acrylate and lauryl acrylate.
[0062] In the present invention, the raw materials for preparing the polyacrylate include 10 to 25 parts of hard monomers by mass, and in specific embodiments, can be 12 parts, 15 parts or 20 parts; the hard monomer is one or more of vinyl acetate, acrylic acid, acrylamide, methyl acrylate and methyl methacrylate.
[0063] In the present invention, the raw materials for preparing the polyacrylate include 1 to 5 parts of functional monomers by mass, and in specific embodiments, may be 2 parts, 3 parts or 4 parts; the functional monomers include one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl methacrylate and N-hydroxyacrylamide.
[0064] In the present invention, the raw materials for preparing the polyacrylate include 0.5 to 1 parts of initiator by mass, and in specific embodiments, it can be 0.6 parts, 0.8 parts or 0.9 parts; the initiator includes one or more of dibenzoyl peroxide, azobisisobutyronitrile and azobisisoheptylonitrile.
[0065] In the present invention, the raw materials for preparing the polyacrylate include 0.5 to 3 parts of a cross-linking agent by mass, and in a specific embodiment, it can be 1 part, 2 parts or 2.5 parts; the cross-linking agent includes one or more of isocyanates, amino resins, metal organic compounds and aziridines, and in a specific embodiment, it can be isocyanates; the isocyanate is Bayer L75.
[0066] In the present invention, the raw materials for preparing the polyacrylate include 50 to 70 parts of an organic solvent by mass, and in a specific embodiment, it can be 55 parts, 60 parts or 65 parts; the solvent includes one or more of ethyl acetate, butanone, acetone, butyl acetate, toluene and xylene.
[0067] In the present invention, the preparation method of the polyacrylate comprises the following steps:
[0068] mixing an organic solvent and an initiator to obtain an initiator mixed solution;
[0069] One third of the initiator mixture is mixed with the remaining raw materials for preparing the polyacrylate, and then one third of the initiator mixture is added for the second time to perform a first polymerization; and then the remaining one third of the initiator mixture is added for a second polymerization to obtain the polyacrylate.
[0070] In the present invention, the second one-third of the initiator mixture is added dropwise for 2 to 4 hours; the remaining one-third of the initiator mixture is added dropwise for 1 to 2 hours; the temperatures of the first polymerization and the second polymerization are independently 80 to 90°C, and the insulation time is 1 to 3 hours, and in a specific embodiment, it can be 2 hours.
[0071] In the present invention, the preparation method of the polyacrylate adhesive comprises the following steps:
[0072] The surface hyperbranched modified fiber and the flame retardant are dispersed in polyacrylate to obtain the polyacrylate adhesive.
[0073] The present invention has no special limitation on the frequency and time of the dispersion, as long as uniform dispersion is achieved. In a specific embodiment, a high-speed disperser is used for uniform mixing.
[0074] The present invention also provides the use of the polyacrylate adhesive described in the above technical solution in packaging materials. In a specific embodiment, it can be an aerosol packaging material.
[0075] In order to further illustrate the present invention, the surface hyperbranched modified fiber and its preparation method, polyacrylate adhesive and its application provided by the present invention are described in detail below in combination with the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0076] The specific preparation steps of the para-aramid fiber paper in the following embodiments of the present invention are as follows:
[0077] Add dissolved N-methylpyrrolidone into the reactor, add 12wt% calcium chloride solution while stirring under the protection of nitrogen, and heat to 80°C to completely dissolve the solubilizing salt to obtain a first solution; cool the first solution to 25°C, add 2g of p-phenylenediamine and 1g of polyoxyethylene ether polymer (molecular weight 6000) to obtain a second solution; after the p-phenylenediamine and calcium chloride in the second solution are completely dissolved, cool to 0°C, add 1.012g of terephthaloyl chloride powder, and stir at high speed at 1000rpm and 80°C to carry out polycondensation reaction, stop stirring when the polycondensation reaction is carried out to form a jelly, that is, a flowable gel state, and the viscosity is between 10000 and 50000cps, add 10 times the weight of N-methylpyrrolidone to the polycondensation reaction system, and stir at high speed at 1000rpm to break up the reactants and homogenize them to obtain macroscopically uniform para-aramid fibers;
[0078] The para-aramid fiber dispersion is repeatedly washed with water using a high-speed centrifuge, and finally dispersed with deionized water under stirring to obtain a para-aramid fiber slurry with a mass concentration of 10%;
[0079] The para-aramid fiber slurry is coated on a 300-mesh forming net to obtain wet paper, and the wet paper is peeled off from the forming net by vacuum adsorption transfer, and the wet paper after peeling is dehydrated by a double-roller double-felt pressing method, and is dried at 60°C for 5 minutes by an electromagnetic heating roller, and finally calendered at 350°C to obtain para-aramid fiber paper.
[0080] Example 1
[0081] 0.5 g of para-aramid fiber paper was immersed in acetone, petroleum ether and deionized water in turn, and refluxed for cleaning for 3 hours. After cleaning, it was taken out and dried at 80°C for 12 hours to obtain clean para-aramid nano-paper.
[0082] 10.5 g of sodium hydroxide was stirred and dissolved in 120 mL of ethanol to obtain a sodium hydroxide-ethanol solution; 0.5 g of clean para-nano aramid paper was immersed in the sodium hydroxide-ethanol solution and refluxed for 5 hours; after the reaction, the obtained product was washed with water and dried in sequence to obtain amino aramid fiber;
[0083] Under the protection of nitrogen atmosphere, 0.1 g of amino-containing aramid fiber, 30 mL of γ-glycidyloxypropyltrimethoxysilane and 150 mL of anhydrous ethanol were added into a 250 mL three-necked flask, and refluxed at 70 ° C for 12 h to obtain methoxylated aramid fiber;
[0084] 14.9 g of cerium chloride and 1.11 g of calcium chloride were dissolved in 150 mL of deionized water to obtain a cerium chloride-calcium chloride mixed solution, 6 g of sodium hydroxide was added to the mixed solution to generate a precipitate, and then 3 mL of hydrogen peroxide was added dropwise, and the pH value of the solution was adjusted to 12 with NaOH; the mixture was reacted at 40° C. for 20 h, and the obtained product was filtered, washed, dried at 120° C. and ground in sequence, and then calcined at 700° C. for 1 h to obtain a milky yellow calcium oxide-doped cerium oxide powder; the calcium oxide-doped cerium oxide powder prepared above was mixed with 15 mL of hydrogen peroxide, reacted at 60° C. for 6 h, and dried after solid-liquid separation to obtain hydroxylated calcium oxide-doped cerium oxide;
[0085] 0.1 g of methoxylated aramid fiber, 0.595 g of hydroxylated calcium oxide doped cerium oxide and 1 g of 38 wt% hydrochloric acid were mixed and refluxed at 65° C. for 6 h to obtain aramid fiber coated with hydroxylated calcium oxide doped cerium oxide;
[0086] Under a nitrogen atmosphere, 0.1 g of aramid fiber coated with hydroxylated calcium oxide doped with cerium oxide, 47.2 g of γ-glycidyloxypropyltrimethylsilane, 5.4 g of 38 wt% hydrochloric acid and 1.3 g of deionized water were added into a three-necked flask and reacted at 70°C for 5 h. After the reaction was completed, the fiber was taken out, washed and dried in sequence to obtain surface hyperbranched modified aramid fiber.
[0087] Example 2
[0088] 1 part of azobisisoheptanenitrile, 50 parts of ethyl acetate and 20 parts of toluene were mixed evenly to obtain an initiator mixture;
[0089] Take one third of the initiator mixture and add it to the reactor, stir and heat it to 88°C, add 70 parts of butyl acrylate, 8 parts of acrylic acid, 4 parts of methyl acrylate and 1 part of 2-hydroxyethyl acrylate to the constant pressure dropping funnel, take another one third of the initiator mixture and add it to the constant pressure dropping funnel, mix the materials in the constant pressure dropping funnel evenly, and add it to the reactor by uniformly dropping, the dropping time is 3h, and the heat preservation polymerization is carried out after the dropping is completed, and the heat preservation time is 2h. After the polymerization, add the remaining initiator mixture to the constant pressure dropping funnel, drop it for 1h, carry out secondary initiation polymerization, keep it warm for 2h, and cool it down to obtain polyacrylate;
[0090] 100 parts of the above polyacrylate, 10 parts of the surface hyperbranched modified aramid fiber obtained in Example 1 and 2 parts of aluminum hydroxide were weighed and mixed evenly using a high-speed disperser to obtain a polyacrylate adhesive.
[0091] Example 3
[0092] Mix 1 part of azobisisoheptanenitrile, 40 parts of ethyl acetate and 30 parts of toluene to obtain an initiator mixture;
[0093] Add one third of the initiator mixture into the reactor, stir and heat to 90°C, add 50 parts of isooctyl acrylate, 10 parts of butyl acrylate, 10 parts of acrylic acid, 4 parts of methyl acrylate, 1 part of 2-hydroxypropyl acrylate and 1 part of glycidyl methacrylate into a constant pressure dropping funnel, take one third of the initiator mixture and add it into the constant pressure dropping funnel, mix the materials in the constant pressure dropping funnel evenly, and add it into the reactor by uniform dropwise addition, the dropping time is 4 hours, and the heat preservation polymerization is carried out after the dropping is completed, and the heat preservation time is 1.5 hours. After the polymerization, add the remaining initiator mixture into the constant pressure dropping funnel, drop it for 1 hour, carry out secondary initiation polymerization, keep it warm for 2 hours, and cool it down to obtain polyacrylate;
[0094] 100 parts of the above polyacrylate, 15 parts of the surface hyperbranched modified aramid fiber obtained in Example 1 and 2 parts of aluminum hydroxide were weighed and mixed evenly using a high-speed disperser to obtain a polyacrylate adhesive.
[0095] Example 4
[0096] Mix 1 part of azobisisoheptanenitrile, 40 parts of ethyl acetate and 30 parts of toluene to obtain an initiator mixture;
[0097] Add one third of the initiator mixture into the reactor, stir and heat to 90°C, add 40 parts of isooctyl acrylate, 10 parts of butyl acrylate, 8 parts of lauryl acrylate, 10 parts of acrylic acid, 4 parts of methyl methacrylate and 3 parts of 2-hydroxyethyl acrylate into a constant pressure dropping funnel, take one third of the initiator mixture and add it into the constant pressure dropping funnel, mix the materials in the constant pressure dropping funnel evenly, and add it into the reactor by uniform dropwise addition, the dropping time is 3.5h, and the heat preservation polymerization is carried out after the dropping is completed, and the heat preservation time is 1h. After the polymerization, add the remaining initiator mixture into the constant pressure dropping funnel, drop it for 1h, carry out secondary initiation polymerization, keep it warm for 1.5h, and cool it down to obtain polyacrylate;
[0098] 100 parts of the above polyacrylate, 20 parts of the surface hyperbranched modified aramid fiber obtained in Example 1 and 2 parts of aluminum hydroxide were weighed and mixed evenly using a high-speed disperser to obtain a polyacrylate adhesive.
[0099] Example 5
[0100] 1 part of azobisisoheptanenitrile, 50 parts of ethyl acetate and 10 parts of butyl acetate were mixed evenly to obtain an initiator mixture;
[0101] Add one third of the initiator mixture into the reactor, stir and heat to 88°C, add 60 parts of butyl acrylate, 5 parts of ethyl acrylate, 5 parts of lauryl acrylate, 8 parts of methyl acrylate, 1 part of acrylamide, 5 parts of vinyl acetate, and 2 parts of 2-hydroxyethyl methacrylate into a constant pressure dropping funnel, take one third of the initiator mixture and add it into the constant pressure dropping funnel, mix the materials in the constant pressure dropping funnel evenly, and add it into the reactor by uniformly dropping, the dropping time is 2.5h, and the heat preservation polymerization is carried out after the dropping is completed, and the heat preservation time is 2h. After the polymerization, add the remaining initiator mixture into the constant pressure dropping funnel, drop it for 2h, carry out secondary initiation polymerization, keep it warm for 2h, and cool it down to obtain polyacrylate;
[0102] 100 parts of the above polyacrylate, 20 parts of the surface hyperbranched modified aramid fiber obtained in Example 1 and 2 parts of aluminum hydroxide were weighed and mixed evenly using a high-speed disperser to obtain a polyacrylate adhesive.
[0103] Example 6
[0104] 1 part of azobisisoheptanenitrile, 50 parts of ethyl acetate and 10 parts of butyl acetate were mixed evenly to obtain an initiator mixture;
[0105] Add one third of the initiator mixture into the reactor, stir and heat to 88°C, add 60 parts of butyl acrylate, 5 parts of ethyl acrylate, 5 parts of lauryl acrylate, 8 parts of methyl acrylate, 1 part of acrylamide, 5 parts of vinyl acetate, and 2 parts of 2-hydroxyethyl methacrylate weighed into a constant pressure dropping funnel, take one third of the initiator mixture and add it into the constant pressure dropping funnel, mix the materials in the constant pressure dropping funnel evenly, and add it into the reactor by uniformly dropping, the dropping time is 2.5h, and the heat preservation polymerization is carried out after the dropping is completed, and the heat preservation time is 2h. After the polymerization, add the remaining initiator mixture into the constant pressure dropping funnel, drop it for 2h, carry out secondary initiation polymerization, keep it warm for 2h, cool it down, and obtain polyacrylate;
[0106] 100 parts of polyacrylate, 30 parts of the surface hyperbranched modified aramid fiber obtained in Example 1 and 2 parts of aluminum hydroxide were weighed by weight, and mixed evenly using a high-speed disperser to obtain a polyacrylate adhesive.
[0107] Example 7
[0108] 1 part of azobisisoheptanenitrile, 30 parts of ethyl acetate, 20 parts of butyl acetate and 10 parts of toluene were mixed evenly to obtain an initiator mixture;
[0109] Add one third of the initiator mixture into the reactor, stir and heat to 82°C, add 40 parts of ethyl acrylate, 20 parts of butyl acrylate, 5 parts of lauryl acrylate, 12 parts of acrylic acid, 10 parts of vinyl acetate, and 2 parts of 2-hydroxyethyl acrylate into a constant pressure dropping funnel, take one third of the initiator mixture and add it into the constant pressure dropping funnel, mix the materials in the constant pressure dropping funnel evenly, and add it into the reactor by uniformly dropping, the dropping time is 2h, and the heat preservation polymerization is carried out after the dropping is completed, and the heat preservation time is 2h. After the polymerization, add the remaining initiator mixture into the constant pressure dropping funnel, drop it for 1.5h, carry out secondary initiation polymerization, keep it warm for 2h, and cool it down to obtain polyacrylate;
[0110] 100 parts of polyacrylate, 25 parts of the surface hyperbranched modified aramid fiber obtained in Example 1 and 2 parts of aluminum hydroxide were weighed by weight, and mixed evenly using a high-speed disperser to obtain a polyacrylate adhesive.
[0111] Test Case
[0112] The performance test of the polyacrylate adhesive obtained in Examples 2 to 7 was carried out, and the specific steps were as follows: the polyacrylate adhesive obtained in Examples 2 to 7 and 2 parts of isocyanate crosslinking agent (Bayer L75) were coated on a 36 μm PET film, dried at 120°C for 3 min, the dry adhesive thickness was 25±1 μm, silicone oil film was applied, and post-cured at 50°C for 72 h for testing. The test results are as follows:
[0113] Table 1 Viscosity test results of the materials described in Examples 2 to 7
[0114]
[0115] The viscosity test is based on GB / T20794-2013.
[0116] Table 2 Test results of heat resistance of materials described in Examples 2 to 7
[0117]
[0118] Table 3 Tear force test results of materials described in Examples 2 to 7 after hot pressing
[0119]
[0120] Table 4 Flame retardant performance test results of materials described in Examples 2 to 7
[0121] Sample Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 data V0 V0 V0 V0 V0 V0
[0122] The flame retardant test is based on GB 8624-2006 / UL94.
[0123] Table 5 Test results of aging resistance of materials described in Examples 2 to 7
[0124]
[0125] The aging resistance test is carried out under the conditions of double 90 / 2000h, and the 180° peel strength test is based on GB / T2790-1995.
[0126] It can be seen from Tables 1 to 5 that the viscosity of the polyacrylate adhesive prepared by the present invention meets the coating requirements; no residual glue is left after the heat resistance test, indicating that the heat resistance of the glue is good; and when the hot pressing test is performed, it cannot be torn apart, proving that the adhesive force of the glue is strong; the flame retardancy test reaches V0 level, has excellent flame retardancy, and meets the design requirements, that is, a small amount of conventional flame retardant powder (aluminum hydroxide: 2-5%) is added, and after hot pressing at 120-130°C, it has strong adhesion to the substrate (PET), cannot be torn apart, and has good aging resistance.
[0127] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. People can also obtain other embodiments based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A surface hyperbranched modified fiber, characterized in that: The invention comprises aramid fiber and hyperbranched polysiloxane grafted with nano metal oxide particles and coated on the aramid fiber.
2. The surface hyperbranched modified fiber according to claim 1, characterized in that: The structure of the hyperbranched polysiloxane is shown in Formula I:
3. The surface hyperbranched modified fiber according to claim 1, characterized in that: The nano metal oxide particles are calcium oxide-doped cerium oxide particles; The mass ratio of calcium oxide to cerium oxide is 2-15:1-2; The particle size of the nano metal oxide particles is 100-300 nm.
4. The surface hyperbranched modified fiber according to any one of claims 1 to 3, characterized in that: The mass ratio of the hyperbranched polysiloxane to the aramid fiber is 200-400:1-2; the mass ratio of the nano metal oxide particles to the hyperbranched polysiloxane is 5-15:1-3.
5. The method for preparing the surface hyperbranched modified fiber according to any one of claims 1 to 4, characterized in that: The following steps are involved: Aramid fibers are subjected to amino modification to obtain amino fibers; The amino fiber is subjected to methoxylation modification to obtain methoxylated fiber; The methoxylated fiber, the hydroxylated metal oxide and the first acid reagent are mixed to perform metal oxide modification to obtain metal oxide coated fibers; The metal oxide coated fiber, γ-glycidyloxypropyltrimethylsilane and a second acid reagent are mixed and subjected to polycondensation reaction to obtain the surface hyperbranched modified fiber.
6. The preparation method according to claim 5, characterized in that: The temperature of the amination modification is 40-80°C and the time is 3-8h; The temperature of the methoxylation modification is 60 to 110° C. and the time is 12 to 18 hours; The metal oxide modification temperature is 60-100°C and the time is 6-12h; The temperature of the polycondensation reaction is 60-90° C. and the time is 5-12 hours.
7. A polyacrylate adhesive, characterized in that: Calculated by weight, it comprises 10 to 40 parts of the surface hyperbranched modified fiber according to any one of claims 1 to 4 or the surface hyperbranched modified fiber prepared by the preparation method according to claim 5 or 6, 2 to 5 parts of a flame retardant and 100 parts of polyacrylate.
8. The polyacrylate adhesive according to claim 7, characterized in that: The polyacrylate comprises the following preparation raw materials by weight: 50-70 parts of soft monomer, 10-25 parts of hard monomer, 1-5 parts of functional monomer, 0.5-1 parts of initiator, 0.5-3 parts of crosslinking agent and 50-70 parts of organic solvent.
9. The polyacrylate adhesive according to claim 8, characterized in that: The soft monomer includes one or more of butyl acrylate, isooctyl acrylate, ethyl acrylate and lauryl acrylate; The hard monomer includes one or more of vinyl acetate, acrylic acid, acrylamide, methyl acrylate and methyl methacrylate; The functional monomers include one or more of 2-hydroxyethyl acrylate, 2-hydroxypropyl acrylate, 2-hydroxyethyl methacrylate, 2-hydroxypropyl methacrylate, glycidyl methacrylate and N-hydroxyacrylamide.
10. Use of the polyacrylate adhesive according to any one of claims 7 to 9 in packaging materials.